Multiscale biomechanics of the biphasic articular cartilage in the natural hip joint during routine activities. (March 2022) - Hua, Xijin; Li, Junyan; De Pieri, Enrico; Ferguson, Stephen J.
Highlights: A multiscale modelling enables the evaluation of cartilage under subject-specific physiological loading. The interstitial fluid pressure supports most of loading during routine activities. The temporal variation of the cartilage contact pressure and fluid pressure shows a location-dependant response during routine activities. The cartilage biphasic behaviour is synergistically affected by the creep of cartilage and the support ratio of the interstitial fluid. Abstract: Background and objective: The investigation of the biomechanical behaviour of the articular cartilage (AC) under physiological loading is important to understand the joint function and onset of pathologies. This study aimed to develop a multiscale computational modelling approach and apply the approach to investigate the time-dependant biphasic behaviour of the AC in the natural hip joint under repetitive physiological loading over 80 cycles amongst six routine activities. Methods: A subject-specific musculoskeletal multibody dynamics (MBD) model was developed based on the anthropometry and motion capture data collected for a male subject. A corresponding FE model of the natural hip joint with biphasic AC was created based on the bone geometries exported from the MBD model. A multiscale computational modelling was then developed to couple the MBD model and the FE model and used to investigate the time-dependant biphasic behaviour of the AC under subject-specific physiological loading over 80 cycles amongst six routine activities. Results: The results showed that for all the activities considered, the interstitial fluid pressure in the AC supported over 80% of the loading. The maximum values of the peak contact pressure and peak fluid pressure for the whole cycle increased firstly and then remained stable over time from the 1st cycle to the 80th cycle. At these instants, the contact areas were located at the centre region of the AC. By contrast, when the contact area was located at the edge of the AC, these peak pressures were found to increase over time for some of the activities (squat, ascending stairs, descending stairs) but decrease for the other activities (normal walking, standing up, sitting down). Conclusion: This study for the first time developed a multiscale computational modelling approach to couple a musculoskeletal MBD model of the body and a detailed FE model of the natural hip joint with biphasic AC, which enabled the evaluation of time-dependant biphasic behaviour of the AC under realistic physiological loading conditions. The study may have important implications in biomechanical studies of human cartilage to understand the joint function and biomechanical factors related to joint disease, and to support the development of cartilage substitution.